Multidisciplinary Design Optimization of Low Wind Speed Wind Turbine - WANG Dian; WU Faming; WANG Lei; LI Huixin (Kongzhi Yu Xinxi Jishu)
It discusses the relationship between characteristics of wind resource and aerodynamics, structural dynamics, structure, control performance, power performance of wind turbine. Model of multidisciplinary design optimization for low wind speed wind turbine is presented with the cost of electricity(COE) and combined ratio as the objective function. To meet the performance requirements of the optimal solution, it searches the best combination of parameters of low wind speed wind turbines. Multidisciplinary design optimization during product concept design stage can improve the comprehensive performance, shorten the development cycle and enhance competitiveness of wind power products.